The analysis of delta-9-tetrahydrocannabinol, cannabidiol and cannabinol in oral fluid and selected commercial products by gas chromatography-mass spectrometry - Laurens, Johannes B. (University of Pretoria, 2022)
Dissertation (MSc (Chemistry))--University of Pretoria, 2022.